Pengaruh Strategi Komunikasi Pemasaran Terhadap Consumer Purchase Decision Dompet Digital - Rahman, Andri Ali; Baskara, Ika (MES Bogor, 2025)
This study aims to analyze the influence of marketing communication strategies on consumer purchase decisions on digital wallet services. An effective marketing communication strategy is a key factor in increasing consumer interest and purchase decisions in today's digital era. The research method used is a quantitative method with data collection through a questionnaire survey to a number of respondents who use digital financial services. The results of the study show that marketing communication strategies that include advertising, sales promotion, direct marketing, social media communication, and personal sales have a significant influence on consumer purchase decisions. These findings indicate that the use of the right communication strategy can increase consumer understanding of digital wallet services and encourage positive purchase decisions. The study concludes that digital financial service providers need to design targeted and measurable marketing communication strategies to maximize consumer purchase decisions. The practical implications of this study can be used as a guide for digital wallet industry players in designing more effective marketing campaigns in the future.